Natural history of KBG syndrome in a large European cohort. Issue 24 (21st July 2022) - Loberti, Lorenzo; Bruno, Lucia Pia; Granata, Stefania; Doddato, Gabriella; Resciniti, Sara; Fava, Francesca; Carullo, Michele; Rahikkala, Elisa; Jouret, Guillaume; Menke, Leonie A; Lederer, Damien; Vrielynck, Pascal; et al.
Abstract: KBG syndrome (KBGS) is characterized by distinctive facial gestalt, short stature and variable clinical findings. With ageing, some features become more recognizable, allowing a differential diagnosis. We aimed to better characterize natural history of KBGS. In the context of a European collaborative study, we collected the largest cohort of KBGS patients (49). A combined array- based Comparative Genomic Hybridization and next generation sequencing (NGS) approach investigated both genomic Copy Number Variants and SNVs. Intellectual disability (ID) (82%) ranged from mild to moderate with severe ID identified in two patients. Epilepsy was present in 26.5%. Short stature was consistent over time, while occipitofrontal circumference (median value: −0.88 SD at birth) normalized over years. Cerebral anomalies, were identified in 56% of patients and thus represented the second most relevant clinical feature reinforcing clinical suspicion in the paediatric age when short stature and vertebral/dental anomalies are vague. Macrodontia, oligodontia and dental agenesis (53%) were almost as frequent as skeletal anomalies, such as brachydactyly, short fifth finger, fifth finger clinodactyly, pectus excavatum/carinatum, delayed bone age. In 28.5% of individuals, prenatal ultrasound anomalies were reported. Except for three splicing variants, leading to a premature termination, variants were almost all frameshift. Our results, broadening the spectrum of KBGS phenotype progression, provide useful tools to facilitate differential diagnosis and improve clinical management. We suggest to consider a wider range of dental anomalies before excluding diagnosis and to perform a careful odontoiatric/ear-nose-throat (ENT) evaluation in order to look for even submucosal palate cleft given the high percentage of palate abnormalities. NGS approaches, following evidence of antenatal ultrasound anomalies, should include ANKRD11.